Factors Affecting Non-Adherence to Secondary Stroke Prevention Therapy in Ischemic Stroke Patients - Zakky Cholisoh; Hidayah Karuniawati; Tanti Azizah; Zaenab Zaenab; Laila Nur Hekmah (Faculty of Pharmacy, Universitas Gadjah Mada)
Stroke is cardiovascular disease that causes the world's highest disability and is the most prevalence disease after heart disease and cancer. Stroke is caused by circulatory disorders with 80% of the sufferers are diagnosed with ischemic stroke and 20% of them are diagnosed with hemorrhagic stroke. Patients who survive from the first stroke have high risk to have recurrent stroke. American Heart Association/American Stroke Association and Perhimpunan Dokter Spesialis Syaraf Indonesia recommend secondary stroke prevention therapy including antiplatelet/anticoagulant, antihypertensive agents, and antidislipidemia to minimalize the risk of recurrent stroke. Secondary stroke prevention therapy is only the first step. Patients need to be adhere to those therapies. The non-adherence will increase the risk of recurrent stroke. The study aimed to determine factors which causing the non-adherence to secondary prevention therapy in patients with ischemic stroke. This was a case control study with concecutive sampling method by interviewing patients who met the inclusion criterias i.e., had been diagnosed and were inpatients due to ischemic stroke, but in the time of interview patients were outpatients, patients were able to communicate and agree to participate in the study.Data was analized by bivariate / chi square test and multivariate logistic regression test. During the study period, 184 respondents met the inclusion criterias. Factors affecting non-adherence in the use of secondary prevention therapy were No one reminded to take medicine p = 0.03; OR 4.51, denial of the disease p = 0,036 OR 214, and tired of taking medicine p = 0,045 OR 1,97.